Contribution of Tibetan Scholars in Indian Pramāṇa Study (Bodhi Path, 2024)
Buddhism was founded by Lord Buddha in the land of diverse philosophies, India. Buddhism is the only Indian religion that expanded and received high privilege beyond the Indian sub-continent such as China, Tibet, Japan, and Mongolia. Scholars from these countries travelled to India to study Buddhist philosophy, which helped in the systematic development of Buddhism in their countries. Among these countries, Buddhist logic and epistemological study, which is known as the Buddhist pramāṇa study, received the highest popularity in Tibet. Tibetan scholars studied the Buddhist pramāṇa system from Indian masters and spread it to their country. Early Tibetan scholars such as Nog Lotsawa Loden Sherab (Rngog Lo Tsaba Blo Ldan Shes rab), Ma Lotsawa Gebai Lodoe (rMa lo-tsa-ba dge-ba'i blo-gros), Phya-pa Chos-kyi Seng-ge, Sa skya Pandita and Gyaltsab Dharma Rinchen (rGyal-tshab Dar-ma Rin-chen), etc made huge contributions to spread and revive Indian Buddhist pramāṇa system, which was declining in India at that time. Most of the Tibetan rulers encouraged and assisted in expanding the Buddhist Pramāṇa study. For instance, the 8th-century Tibetan king Trisong Detsen (Khri-Song lDe’u-bTsen) not only invited Indian scholar Śāntarakṣita to promote Buddhism but also wrote a pramāṇa text called Kah Yang Dagpai Tshadma ( bKa’ yang dag-pa’i tshad-ma). This shows his high interest in Buddhism and Buddhist logic. The translation of Buddhist texts especially Buddhist pramāṇa texts was initiated before the 10th century but proper theorizing began in the 10th and 11th centuries. Tibetan translators with the help of Indian scholars initiated the translation of Indian canonical and non-canonical texts and gradually made Tibetan commentary on Indian pramāṇa texts. Those translated and commentarial texts play an eminent role in preserving the writings of ancient Indian scholars, for instance, the original Sanskrit version of Dignāga’s Pramāṇasamuccaya  text is not available but the translated Tibetan version is available in contemporary times.                                          Tibetan scholars invented new methods in pramāṇa study, the Tibetan debate method and also invented the Collected topics (bsdus grwa) texts. The collected topics are the basic text of the pramāṇa study, where the summarization of Buddhist logical topics is collected and written. These two are important contributions of Tibetan scholars in the development of Indian pramāṇa study besides translation and commentary. Indian logical texts of Dignāga, Dharmakīrti, Śāntarakṣita and Kamalaśīla study in Tibetan monasteries especially Pramāṇavārttikā text of Dharmakīrti, which is a root text for Tibetan pramāṇa study in the contemporary times, are studied and analytically debated in Tibetan monasteries.                                                                                                                                        Thus, Tibet and its people made a huge contribution in preserving and promoting Buddhism especially the Buddhist pramāṇa system after it was declined in India. In the paper, the author tries to highlight the contribution of Tibetan scholars in the Buddhist pramāṇa study by presenting the work and achievements of Tibetan scholars. It will also focus on proving whether their work genuinely helps in promoting and reviving of Buddhist pramāṇa system of Indian logicians such as Dignāga and Dharmakīrti.
Keywords: Translation; Commentary; Scholars; Pramāṇa study; Tibet; India